Analisis Kemandirian Belajar Siswa sebagai Dasar Pengembangan Buku Elektronik (e-book) Fisika Terintegrasi Edupark - Yunita, Rika Arni; Hamdi, Hamdi (Jurnal Penelitian Pembelajaran Fisika, 2019)
Physics learning is a natural science that studies phenomena and events in nature. The concept of physics will be better understood by directly observing the events in the surrounding environment. Learning in nature, especially in tourism which is called by edupark will be learning the fun and motivating student to better understand the concepts of physics. Teachers are required to be creative and innovative in the provision of teaching materials that utilize technology. Therefore a analysis of independent student on aspects of knowledge, skills and style of learning. The data of this study were taken with questionnaires with students at SMAN 1Talamau, SMAN 1 Pasaman and SMAN 2 Pasaman. Analysis of preliminary describe the student has not been independent and has not been able to resolve the problem that is encountered in learning, students enjoy the learning on the tourism and students like learning with electronic books (e-book). For this reason, it is necessary to carry out research into the development of an integrated e-book edupark to improve student learning independence.